2011
DOI: 10.1103/physrevb.84.235119
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio27Al NMR chemical shifts and quadrupolar parameters for Al2O3phases and their precursors

Abstract: The Gauge-Including Projector Augmented Wave (GIPAW) method, within the Density Functional Theory (DFT) Generalized Gradient Approximation (GGA) framework, is applied to compute solid state NMR parameters for 27 Al in the α, θ, and κ aluminium oxide phases and their gibbsite and boehmite precursors. The results for well-established crystalline phases compare very well with available experimental data and provide confidence in the accuracy of the method. For γ-alumina, four structural models proposed in the lit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 65 publications
2
18
0
1
Order By: Relevance
“…The chemical shielding tensors (σ) were calculated using gauge-including projector augmented waves (GIPAW). This method was based on DFT to calculate magnetic resonance properties, exploiting the full translational symmetry of crystals (Pickard & Mauri, 2001), (Yates et al, 2007), (Ferreira et al, 2011). Interaction of valence electrons with nuclei and core electrons is treated by the projector augmented-wave (PAW) method.…”
Section: Theoretical Methodologymentioning
confidence: 99%
“…The chemical shielding tensors (σ) were calculated using gauge-including projector augmented waves (GIPAW). This method was based on DFT to calculate magnetic resonance properties, exploiting the full translational symmetry of crystals (Pickard & Mauri, 2001), (Yates et al, 2007), (Ferreira et al, 2011). Interaction of valence electrons with nuclei and core electrons is treated by the projector augmented-wave (PAW) method.…”
Section: Theoretical Methodologymentioning
confidence: 99%
“…Several computational studies on aluminum oxide polymorphs have been reported in recent years, which mainly apply standard DFT methods. [22][23][24][25][26][27][28][29][30] In this paper, we apply a recently developed technique based on the so-called quasi-harmonic approximation (QHA): a simple and effective method that is able to address the aforementioned issue in the case of corundum. 31,32 The thermal expansion coefficient, α(T ), heat capacities, C V (T ) and C P (T ), entropy, S(T ) and bulk modulus, K(T ) of corundum are calculated in its entire range of thermal stability (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of a-Al 2 O 3 has been actively discussed from the short-and medium-range point-of-view by x-ray photoelectron 12,13 and Auger electron 12 spectroscopy, extended x-ray absorption fine structure technique, 14 transmission electron microscopy, 15,16 nuclear magnetic resonance spectroscopy, 17 and also by a number of theoretical approaches. [18][19][20][21][22] On the other hand, few studies have been reported for a-Ta 2 O 5 and a-Nb 2 O 5 . [23][24][25] In this study, the diffusivity of the common element, oxygen, in a-Al 2 O 3 , a-Ta 2 O 5 , and a-Nb 2 O 5 was investigated.…”
Section: Introductionmentioning
confidence: 99%